Otomatisasi Pengujian Aplikasi Web Otten Coffee Menggunakan Katalon Studio - Desyani, Teti; syamsiana, Andika; Kobun, Elisabet Ukung; Ananda, Frisca Tri; Priaji, Sugeng; Yulianti, Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Otten Coffee is an application designed to make it easier for customers to shop for the coffee they want. The Otten Coffee application continues to develop its features and to ensure these features work properly, testing is needed to ensure the quality of the application is maintained. This research was conducted to create a convenient system for users to use in creating a pleasant shopping experience on the Otten Coffee website. In this study, manual testing / Black-box testing and automatic testing were carried out using Katalon Studio as an automation testing tool. Black-box testing is a type of testing method that treats software whose internal performance is unknown. Black-box testing itself is a kind of test that treats application programs whose overall performance is ignored where we only see the external performance of the application, this test is felt to be necessary to look for bugs and damage to our application before it is launched. As well as testing using Katalon Studio, namely all systems tested produce output that is in accordance with what the website developer wants.